THE CONCEPT OF INFORMATION AND EDUCATIONAL ENVIRONMENT IN THE CONTEXT OF UPDATED EDUCATION - Gussenova, S.Sh.; Babaev, D.B.; Smagulov, E.Zh. (Scientific Journal of Pedagogy and Economics, 2020)
Currently, there is a rapid development of information technologies, the restructuring of the system of education and upbringing of the younger generation to a new level. All this forces modern society to move forward, keep up with scientific and technological progress and time. Today, the key issue of modernizing education is to improve its quality and bring it in line with international standards. The emphasis is not on the acquired knowledge, but on the process of applying this knowledge. The article deals with the main directions of development of the education system and theoretical aspects of the development of the information and educational environment in the context of updated education. A new generation of school children can easily master any new digital and multimedia technology. Teachers are tasked with directing the student's development vector in the right direction. To do this, methods of working with students are being improved. The article describes pedagogical technology as information technology, since the basis of the technological process of learning is the acquisition and transformation of information. The paper considers a single information and educational space that can provide students with the opportunity to use a wide range of educational content (electronic textbooks, video courses, etc.), using interactive technologies to compensate for gaps in education, to realize their creative abilities through participation in various competitions, olympiads, festivals, conferences. Use the system of additional education without interrupting training due to various factors. The Internet environment for teenagers has long been clear and close, and it is believed that it can become a productive platform for improving education. As one of the areas of relevance of the research, the authors will determine the current trends in the development of computer science as a science, in particular, the transition to e-learning in the framework of updated education. The developers of modern educational standards emphasize the need to create an information and educational environment (IEE) in educational organizations that ensures the formation of universal educational actions of students. Thus, the understanding of the environment as a field of obtaining information is replaced by the understanding of the environment as a field of constructing ways of students ' activities. Such an environment from the point of view of the conducted research should be created on the basis of the system integration of ICT tools into the traditional educational environment. The complexity of the work of teachers is due to the lack of a unified model of integrative IEE in educational organizations. The search for effective ways to integrate traditional and innovative environments largely depends on the activities of subject teachers, who are able to turn the potential of the subject-oriented IEE to achieve qualitatively new educational results. The article presents a theoretical description of integrative activity-based IEE, which can serve as a basis for innovative activity of teachers. The article reveals the content and structure of the information and educational environment. The leading approaches to defining the concept of information and educational environment in pedagogical science are substantiated. The features of creating this environment in a secondary school are revealed. The authors conclude that the creation of an information and educational environment is one of the most important indicators of the quality of the education system.